-
Сумма синусов
\(\sin \alpha + \sin \beta = 2\sin \large\frac{{\alpha + \beta }}{2}\normalsize \cos \large\frac{{\alpha - \beta }}{2}\normalsize\)
-
Разность синусов
\(\sin \alpha - \sin \beta = 2\cos \large\frac{{\alpha + \beta }}{2}\normalsize \sin \large\frac{{\alpha - \beta }}{2}\normalsize\)
-
Сумма косинусов
\(\cos \alpha + \cos \beta = 2\cos \large\frac{{\alpha + \beta }}{2}\normalsize \cos \large\frac{{\alpha - \beta }}{2}\normalsize\)
-
Разность косинусов
\(\cos \alpha - \cos \beta = -2\sin \large\frac{{\alpha + \beta }}{2}\normalsize \sin \large\frac{{\alpha - \beta }}{2}\normalsize\)
-
Сумма тангенсов
\(\tan\alpha + \tan \beta = \large\frac{{\sin \left( {\alpha + \beta } \right)}}{{\cos \alpha \cdot \cos \beta }}\normalsize\)
-
Разность тангенсов
\(\tan\alpha - \tan \beta = \large\frac{{\sin \left( {\alpha - \beta } \right)}}{{\cos \alpha \cdot \cos \beta }}\normalsize\)
-
Сумма котангенсов
\(\cot\alpha + \cot \beta = \large\frac{{\sin \left( {\beta + \alpha } \right)}}{{\sin \alpha \cdot \sin \beta }}\normalsize\)
-
Разность котангенсов
\(\cot\alpha - \cot \beta = \large\frac{{\sin \left( {\beta - \alpha } \right)}}{{\sin \alpha \cdot \sin \beta }}\normalsize\)
-
Сумма косинуса и синуса
\(\cos\alpha + \sin \alpha = \sqrt 2 \cos \left( {\large\frac{\pi }{4}\normalsize - \alpha } \right) = \sqrt 2 \sin\left( {\large\frac{\pi }{4}\normalsize + \alpha } \right)\)
-
Разность косинуса и синуса
\(\cos\alpha - \sin \alpha = \sqrt 2 \sin \left( {\large\frac{\pi }{4}\normalsize - \alpha } \right) = \sqrt 2 \cos\left( {\large\frac{\pi }{4}\normalsize + \alpha } \right)\)
-
Сумма тангенса и котангенса
\(\tan\alpha + \cot \beta = \large\frac{{\cos \left( {\alpha - \beta } \right)}}{{\cos \alpha \cdot \sin \beta }}\normalsize\)
-
Разность тангенса и котангенса
\(\tan\alpha - \cot \beta = -\large\frac{{\cos \left( {\alpha + \beta } \right)}}{{\cos \alpha \cdot \sin \beta }}\normalsize\)
-
\(1 + \cos \alpha = 2\,{\cos ^2}\large\frac{\alpha }{2}\normalsize\)
-
\(1 - \cos \alpha = 2\,{\sin ^2}\large\frac{\alpha }{2}\normalsize\)
-
\(1 + \sin \alpha = 2\,{\cos ^2}\left( {\large\frac{\pi }{4} - \frac{\alpha }{2}\normalsize} \right)\)
-
\(1 - \sin \alpha = 2\,{\sin ^2}\left( {\large\frac{\pi }{4} - \frac{\alpha }{2}\normalsize} \right)\)